2012
DOI: 10.1080/00927872.2011.568993
|View full text |Cite
|
Sign up to set email alerts
|

A Generalization of Commutativity Degree of Finite Groups

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…Moreover, we extend some of the results obtained in [2]. We also develop and characterize a formula for probability of the pair (H, G), which generalizes the formula for Pr (H, G) given in [2]. Note that if H = G then Paut(H, G) = P aut(G), which coincides with autocommutativty degree Paut(G) of G, if we take = 1, the identity element of G. We note that this case is treated in [7].…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, we extend some of the results obtained in [2]. We also develop and characterize a formula for probability of the pair (H, G), which generalizes the formula for Pr (H, G) given in [2]. Note that if H = G then Paut(H, G) = P aut(G), which coincides with autocommutativty degree Paut(G) of G, if we take = 1, the identity element of G. We note that this case is treated in [7].…”
Section: Introductionsupporting
confidence: 81%
“…In this section we first give the following definition which generalizes definitions of Das et al and Moghaddam et al, see [2,6]. Definition 2.1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, Lescot [9] showed that Pr(G 1 ) = Pr(G 2 ) if G 1 and G 2 are isoclinic finite groups. Various generalizations of this result can be found in [3,11,12,14]. Recently, Buckley et.…”
Section: An Invariance Propertymentioning
confidence: 63%